Accessing conjugated and twisted structures for efficient dual-state emission fluorophore and its sensitive lysosomal imaging. (May 2022) - Tan, Manman; Li, Yingzhong; Guo, Weihan; Chen, Yalan; Wang, Mingda; Wang, Yigang; Chi, Baozhu; Wang, Hua; Xia, Guomin; Wang, Hongming
Abstract: Herein, based on 1, 8-naphtholactam, we have developed twisted and conjugated fluorophores, NPM-1 and NPM-2, which featured efficient emissions in both dispersion and aggregation states with quantum yields up to 0.76 and 0.84, respectively. From spectral and density functional theory (DFT) calculation, the luminescence mechanism of both compounds was intramolecular charge transfer (ICT) in this D-A type molecules, and the structural differences lead to differences in the intensity of ICT effects. Moreover, NPM-1 exhibited efficient and stable emissions in a variety of environments due to its rational structural design. It was a sensitive lysosome-targeting dye and retains its fluorescence intensity under continuous laser irradiation. All these features made it an unprecedented chemical tool for real-time monitoring of lysosomal status and changes, leading to a better understanding of physiological and pathological processes. Highlights: A lysosome-targeting dyes with efficient emissions in both dispersion and aggregation states. Highly conjugated and twisted structures enabling high quantum yields. Spectral and density functional theory calculation reveals that the luminescence mechanism is ICT. Sensitive and stable lysosome-targeting ability are demonstrated in the cell imaging.